Case report Thoraco-omphalopagus twins: different perinatal circumstances, different outcome - Piaseczna-Piotrowska, Anna; Chilarski, Andrzej; Krajewski, Wojciech; Godlewska-Tarka, Joanna (Archives of Medical Science, 2010)
Two pairs of omphalopagus twins were encountered at the Polish Mother’s Health Institution in Lodz, Poland during the past 15 years. In the first set the prenatal diagnosis was not established and the delivery of the twins in a regional hospital was a complete surprise. Both babies died. In the second case the conjoined twins were diagnosed prenatally, surgical separation was successful, and both twins survived. The prenatal identification of conjoined twins is of cardinal importance for the planning of delivery and possible separation.